Execution of coordinate based classifier system to predict specific criminal behavior using regional multi person pose estimator - Zaman, Md. Farhan; Tousif, Md. Iftekhar Alam; Monami, Maliha; Hossain, Hazrat Sauda; Hossain, Sanjida (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.